Effect of early-age subfreezing temperature on grouted dowel precast concrete wall connections. (1st June 2017) - Provost-Smith, D.J.; Elsayed, M.; Nehdi, M.L.
Highlights: Effect of subfreezing temperature on grouted dowel connections was explored for the first time. Bond strength was proportional to compressive strength square root after early-age subfreezing. Bond stress-slip response was unchanged after exposure to early-age subfreezing conditions. Initial normal temperature curing period was crucial for grout's compressive strength gain. Abstract: During cold weather precast wall construction, in-situ heating of the grout used in grouted dowel connections is usually conducted for short periods of time. Hence, early-age exposure to subfreezing conditions may affect the quality of the grout and subsequently the bond strength of the connection, which can compromise structural integrity. In this study, grout specimens typical of that used in precast wall construction were initially cured at ambient conditions for one day and then placed inside a walk-in environmental chamber at subfreezing temperatures. The hardened grout properties and bond strength of the connection were examined and compared to that of specimens cured at ambient temperature. The compressive strength of the grout was monitored at temperatures of 1°, −10° and −20 °C. The effect of subfreezing exposure on the mechanical properties, hydration process and pore size distribution of the grout were examined. It was found that early-age subfreezing curing temperatures reduced the compressive strength of the grout, leading to increased dowel embedment length to achieve bar fracture. The bond strength of the connection remained proportional to the square root of compressive strength, even subsequent to early-age exposure to subfreezing temperature.